Pemasaran Jasa Pendidikan IAIN Antasari (Perspektif Marketing Mix Jasa Pendidikan) - Juhaidi Ahmad (Khazanah: Jurnal Studi Islam dan Humaniora, 2015)
Competition among institutions of education to make educational services marketing into an inter- esting study to be observed . This article is the result of quantitative descriptive research with descrip- tive statistical analysis . The study population was all new students IAIN Antasari in 2013 amounted to 1578 people with a stratified sample of 515 people . This research error rate below 1 % . This study found that the elements of the marketing mix is the reason most dominant freshman academic year 2013/2014 to choose IAIN Antasari is a product ( 92.12 % ) and most do not provide the driving is the promotion element ( 62.27 % ) . Thus , the promotion of which has been implemented so far should be evaluated in order to optimize the marketing of educational services IAIN Antasari . Key Wordss : Product, price, place, promotion, people, physical evidence, and process